Tindak Pidana Pembunuhan Berencana dalam Pasal 340 Kitab Undang-Undang Hukum Pidana - Charen Toisuta; Dhea Salsabila; Jason Johanis Walean; Asmak Ul Hosnah (Lembaga Pengembangan Kinerja Dosen, 2023)
The crime of premeditated murder is a term for premeditated murder by a person or a group of people who basically want to kill or eliminate someone's life. The crime of premeditated murder is regulated in the Criminal Code Article 340. The purpose of this writing is to find out what elements are contained in the crime of premeditated murder, whether there are elements of premeditated murder, the purpose of premeditated murder as well as the law or sanctions given and the responsibility of the crime. premeditated murder under Article 340 of the Criminal Code. The method used is library research method. The crime of premeditated murder is listed in the Criminal Code Article 340 with elements of a criminal act who, intentionally, plans ahead and takes the lives of other people. One of the main elements is the planned element. The element of planning in advance means that there is a distance or time between the intention to kill and the execution of the murder and the aim is to make the killing run smoothly. Sanctions for a crime are death penalty, life imprisonment and 20 years temporary imprisonment. A criminal act of premeditated murder must be held responsible for the actions that have been committed.